Family Economic Status and Parental Involvement: Educating Parents using School-Family Partnerships for Student Success in School Context - Putri, Fika Ayu Gustiyani; Yustiana, Yusi Riksa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
This article explores the relationship between family economic status and parental involvement in supporting student success through effective school-family partnerships. Using a qualitative literature review approach, the authors analyzed 29 selected studies 20 qualitative and 9 quantitative published within the past decade. The review reveals that family economic status significantly influences the level and quality of parental involvement in children’s education. Parents from low-income families often face barriers such as limited time, knowledge, and resources, while those from higher economic backgrounds may display selective involvement due to reliance on external support systems. The study highlights that both extremes of economic status can result in reduced collaboration between parents and schools, ultimately affecting student outcomes. The paper emphasizes the importance of teachers’ and counselors’ roles in fostering inclusive, culturally responsive partnerships that bridge economic disparities. By integrating insights from family-systems and school-based counseling perspectives, the study advocates for collaborative models that empower parents regardless of their socioeconomic conditions. The authors conclude that sustainable school-family partnerships can enhance students’ academic achievement, emotional well-being, and long-term development through equitable access to support and engagement